2020
DOI: 10.3390/ma13081954
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Materials Used as Supplementary Cementitious Materials in the Concrete Industry

Abstract: A sustainable solution for the global construction industry can be partial substitution of Ordinary Portland Cement (OPC) by use of supplementary cementitious materials (SCMs) sourced from industrial end-of-life (EOL) products that contain calcareous, siliceous and aluminous materials. Candidate EOL materials include fly ash (FA), silica fume (SF), natural pozzolanic materials like sugarcane bagasse ash (SBA), palm oil fuel ash (POFA), rice husk ash (RHA), mine tailings, marble dust, construction and demolitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 116 publications
(180 reference statements)
1
33
0
Order By: Relevance
“…properties of modified cement matrix composites reinforced with fibers [14,[18][19][20]; • application of new types of supplementary cementitious materials [13,16,[21][22][23][24][25][26][27][28]; • characterization of various types of modified cement based materials [18,21,23,[25][26][27][28][29][30][31].…”
Section: Short Description Of the Articles Presented In This Special Issuementioning
confidence: 99%
“…properties of modified cement matrix composites reinforced with fibers [14,[18][19][20]; • application of new types of supplementary cementitious materials [13,16,[21][22][23][24][25][26][27][28]; • characterization of various types of modified cement based materials [18,21,23,[25][26][27][28][29][30][31].…”
Section: Short Description Of the Articles Presented In This Special Issuementioning
confidence: 99%
“…The voids cause low density and high water absorption [1]. It has been reported that various factors such as the amount and moisture of recycled coarse aggregates (RCA), water to cement ratio, source concrete strength, number of crushing steps, age of primary concrete, and the amount of adhesive mortar have an important effect on regulating the properties of these aggregates [12][13][14][15]. Furthermore, the use of small amounts of recycled fine aggregates, between 6% to 10%, was recommended [16].…”
Section: Introductionmentioning
confidence: 99%
“…The cement production process generates almost 7% of the global greenhouse gas emissions [ 6 , 7 , 8 , 9 , 10 ]. Using waste as supplementary cementitious materials (SCMs) instead of clinker in the technology of cement production and cement in concrete will contribute to the partial solution of the above-mentioned problems [ 11 , 12 , 13 ]. Ground granulated blast-furnace slag and fly ash are among the types of waste that are utilized successfully in the construction industry and are attributed to the supplementary cementitious materials.…”
Section: Introductionmentioning
confidence: 99%